EXPLORE THE IMPACT OF RELIEFS & REBATE ON ITR FOR INDIVIDUALS: A QUALITATIVE STUDY (CAHIERS MAGELLANES-NS, 2024)
The tax revenue is very crucial for the government to undertake development projects and operation of the nation smoothly. The taxpayer directly influenced and impacted their living level through the policy of taxation. The present paper mostly focus on the Impact of Reliefs and rebates on ITR for individuals during a specific period. The study has the main object of identifying the impact as well as the significance of the model that explored to effect of predefined variables on the dependent variables. The study identified significant associations among the selected variables as well as also the significance of certain patterns and structures with selected data under the variables. The logistic regression model also identifies the effect of income as most significant on the Relief-Rebate Positive Impact on ITR rather than such variables as profession, salary and exemption.